Three-dimensional finite element analysis of braced excavation systems - Winata, Berlina Margaretha. (2010)
Braced excavation study is usually modeled using plane strain (two-dimensional) finite element analysis. In this kind of analysis, the length of excavation wall is assumed to be infinitely long, so that the effect of the length of excavation is neglected. However this analysis may not correctly represent the actual scenario of the braced excavation system, especially for the excavation in which the wall length is short.